Identification and Characterization of BMS-955176, a Second-Generation HIV-1 Maturation Inhibitor with Improved Potency, Antiviral Spectrum, and Gag Polymorphic Coverage - Nowicka-Sans, Beata; Protack, Tricia; Lin, Zeyu; Li, Zhufang; Zhang, Sharon; Sun, Yongnian; Samanta, Himadri; Terry, Brian; Liu, Zheng; Chen, Yan; Sin, Ny; Sit, Sing-Yuen; et al. (Antimicrobial agents and chemotherapy, 2016)
BMS-955176 is a second-generation human immunodeficiency virus type 1 (HIV-1) maturation inhibitor (MI). A first-generation MI, bevirimat, showed clinical efficacy in early-phase studies, but ∼50% of subjects had viruses with reduced susceptibility associated with naturally occurring polymorphisms in Gag near the site of MI action. MI potency was optimized using a panel of engineered reporter viruses containing site-directed polymorphic changes in Gag that reduce susceptibility to bevirimat (including V362I, V370A/M/Δ, and T371A/Δ), leading incrementally to the identification of BMS-955176. BMS-955176 exhibits potent activity (50% effective concentration [EC50], 3.9 ± 3.4 nM [mean ± standard deviation]) toward a library (n = 87) of gag/pr recombinant viruses representing 96.5% of subtype B polymorphic Gag diversity near the CA/SP1 cleavage site. BMS-955176 exhibited a median EC50 of 21 nM toward a library of subtype B clinical isolates assayed in peripheral blood mononuclear cells (PBMCs). Potent activity was maintained against a panel of reverse transcriptase, protease, and integrase inhibitor-resistant viruses, with EC50s similar to those for the wild-type virus. A 5.4-fold reduction in EC50 occurred in the presence of 40% human serum plus 27 mg/ml of human serum albumin (HSA), which corresponded well to an in vitro measurement of 86% human serum binding. Time-of-addition and pseudotype reporter virus studies confirm a mechanism of action for the compound that occurs late in the virus replication cycle. BMS-955176 inhibits HIV-1 protease cleavage at the CA/SP1 junction within Gag in virus-like particles (VLPs) and in HIV-1-infected cells, and it binds reversibly and with high affinity to assembled Gag in purified HIV-1 VLPs. Finally, in vitro combination studies showed no antagonistic interactions with representative antiretrovirals (ARVs) of other mechanistic classes. In conclusion, BMS-955176 is a second-generation MI with potent in vitro anti-HIV-1 activity and a greatly improved preclinical profile compared to that of bevirimat.